The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1038/sj.pcan.4500535
|View full text |Cite
|
Sign up to set email alerts
|

Influence of circumcision and sexual behaviour on PSA levels in patients attending a sexually transmitted disease (STD) clinic

Abstract: Early age at first intercourse, increased number of sexual partners, lack of circumcision and history of sexually transmitted diseases (STDs) are associated with prostate cancer. There has been no investigation of the effect of these factors on prostate health at an early age. Previously collected serum samples from STD clinic attendees were tested retrospectively for anti-chlamydial antibodies, and prostate specific antigen (PSA) concentration. Patients at an STD clinic were interviewed regarding age of first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…2,3 Interestingly, in the first of these studies, men's convalescent PSA concentrations remained elevated for at least several months after diagnosis and effective antibiotic therapy, raising the possibility of a longer-term influence of STIs on the prostate. 2 These findings are consistent with those from cross-sectional studies of Chlamydia trachomatis (CT) 4 and human herpesvirus type 8 serology 5,6 that observed positive results with PSA, as well as those from longitudinal studies of men treated for febrile urinary tract infections (UTIs) that observed large PSA rises sustained over several months. 7,8 In addition to genitourinary infections, non-genitourinary and systemic infections have also been found to contribute to elevated serum PSA.…”
supporting
confidence: 77%
“…2,3 Interestingly, in the first of these studies, men's convalescent PSA concentrations remained elevated for at least several months after diagnosis and effective antibiotic therapy, raising the possibility of a longer-term influence of STIs on the prostate. 2 These findings are consistent with those from cross-sectional studies of Chlamydia trachomatis (CT) 4 and human herpesvirus type 8 serology 5,6 that observed positive results with PSA, as well as those from longitudinal studies of men treated for febrile urinary tract infections (UTIs) that observed large PSA rises sustained over several months. 7,8 In addition to genitourinary infections, non-genitourinary and systemic infections have also been found to contribute to elevated serum PSA.…”
supporting
confidence: 77%
“…Viewing our findings in the context of the longer‐term or cumulative influences of current and/or resolved infections rather than the acute influences of infection, our nonsignificant findings are consistent with those from previous cross‐sectional studies of nonlifelong infections ( T. vaginalis and syphilis) that observed null associations with PSA, but differ from those from other cross‐sectional and longitudinal studies that observed positive findings for C. trachomatis serostatus and histories of medical record–confirmed chlamydia and NCNGU diagnoses with PSA concentration and trajectories in younger men . However, in the latter study, positive associations were observed only when PSA trajectories were examined and not when only one PSA measurement was used (% with PSA ≥0.7 ng/mL = 38.3 for chlamydia, 39.6 for gonorrhea, and 31.7 for NCNGU vs 37.1 for controls without these infections; P = 0.772, 0.639, and 0.659, respectively).…”
Section: Discussionsupporting
confidence: 87%
“…Accepting PSA as a marker of prostate inflammation, we postulate that the association between HHV-8 seropositivity and elevated PSA signifies either the effects of HHV-8 infection on prostate inflammation [19] or the effects of prostate inflammation on HHV-8 reactivation. PSA elevation has been observed in relation to other infectious disease agents [36,37]. …”
Section: Discussionmentioning
confidence: 99%